Evaluation of Parameters and Nozzle Tip Damage after Clinical Use of Three Hydrophilic Intraocular Lens Injector Models - Lu Zhang; Sonja Schickhardt; Patrick Merz; Gerd Uwe Auffarth (Journal of Ophthalmology, 2024)
Purpose. To assess the nozzle tip damage and the parameters of three different hydrophilic intraocular lens (IOL) injector models. Methods. After routine cataract surgeries at the University Eye Hospital Heidelberg, all the used IOL injectors were collected from the operating room and sent to our laboratory. Nozzle tip damage was assessed under a microscope and graded as follows: no damage (grade 0), slight scratches (1), deep scratches (2), extensions (3), cracks (4), and bursts (5). Each damage grade was assigned a score from 0 to 5, and the total damage score for each injector system was calculated and compared. Nozzle tip parameters (diameters and areas), plunger tip parameters, and tip angles were also measured in each model. Results. The damage scores were (median, Q3-Q1): 1 (1-1) for Accuject, 1 (1-1) for Bluemixs, and 1 (1-1) for RayOne. There was no statistically significant difference in the damage scores between the study groups (P>0.05). The outer cross-sectional vertical and horizontal diameters were 1.69 and 1.69 mm for Accuject, 1.69 and 1.69 mm for Bluemixs, and 1.70 and 1.71 mm for RayOne. Plunger tip areas were 0.78 mm2 for Accjuect, 0.74 mm2 for Bluemixs, and 0.43 mm2 for RayOne. Plunger tip area/inner cross-sectional area of the nozzle tip (%) was 31.2% for RayOne, 66.7% for Accuject, and 63.8% for Bluemixs. The tip angles for three injector models were 56° (Accuject), 56° (Bluemixs), and 44° (RayOne). Conclusions. All the injector models showed mild to moderate damage to the nozzle tip after IOL implantation, even with smaller diameter tips. RayOne resulted in the lowest ratio between plunger tip area and inner cross-sectional area of the nozzle tip and a better distribution of damage categories than the other two groups. All three injector models had relatively small tip parameters. If smaller incisions are required in certain patients, smaller tip parameters should be considered.